2022
DOI: 10.1161/strokeaha.121.037548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baseline Antihypertensive Treatments on Stroke Severity and Outcomes in the BP TARGET Trial

Abstract: Background: Acute ischemic stroke (AIS) patients with a history of hypertension experience worse outcomes, which may be explained by a deleterious impact of the renin-angiotensin system (RAS) overactivation. We sought to investigate whether prestroke antihypertensive treatments (AHT) influenced baseline stroke severity and neurological outcomes, in patients with AIS successfully treated by endovascular therapy. Methods: We performed a post hoc analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…ARB was also beneficial in reducing the incidence of ischemic stroke and improving clinical outcomes. A post hoc analysis of the BP-TARGET trial found that patients treated with ARB before stroke exhibited less severe stroke and developed less intracranial hemorrhage at 24 h. 7 The potential mechanism could be explained by renin-angiotensin system (RAS) blockage, which leads to decreased intra- cranial hemorrhage (ICH). 40 Patients taking a RAS inhibitor also tended to have more neurological improvement compared with the non-RAS inhibitor group, which could be partially explained by a higher rate of ICH in the group of patients who had no RAS inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARB was also beneficial in reducing the incidence of ischemic stroke and improving clinical outcomes. A post hoc analysis of the BP-TARGET trial found that patients treated with ARB before stroke exhibited less severe stroke and developed less intracranial hemorrhage at 24 h. 7 The potential mechanism could be explained by renin-angiotensin system (RAS) blockage, which leads to decreased intra- cranial hemorrhage (ICH). 40 Patients taking a RAS inhibitor also tended to have more neurological improvement compared with the non-RAS inhibitor group, which could be partially explained by a higher rate of ICH in the group of patients who had no RAS inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Pre-stroke use of antihypertensive drugs is also related with better clinical outcomes. 7 However, whether genetic predisposition leads to less severe stroke or better clinical outcomes after ischemic stroke onset remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A post-hoc analysis of the BP-TARGET trial found that patients treated with ARB before stroke exhibited less severe stroke and developed less intracranial hemorrhage at 24 hours. (7) The potential mechanism could be explained by RAS blockage, which leads to decreased ICH. (39) Patients taking a RAS inhibitor also tended to have more neurological improvement compared with the non-RAS inhibitor group, which could be partially explained by a higher rate of ICH in the group of patients who had no RAS inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…(39) Patients taking a RAS inhibitor also tended to have more neurological improvement compared with the non-RAS inhibitor group, which could be partially explained by a higher rate of ICH in the group of patients who had no RAS inhibitor. (7) Given the short half-life of antihypertensive drugs, there is the possibility that the biological effects of these baseline antihypertensive drugs only last a few hours during the acute phase, and thereafter, is insufficient to impact 3-month outcomes. In this MR analysis, previous use of ACEI showed a robust effect on improving 3-month clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation